Are context-specific measures of parental-reported physical activity and sedentary behaviour associated with accelerometer data in 2–9-year-old European children?. Issue 5 (2nd June 2014) - Verbestel, Vera; De Henauw, Stefaan; Bammann, Karin; Barba, Gianvincenzo; Hadjigeorgiou, Charalambos; Eiben, Gabriele; Konstabel, Kenn; Kovács, Eva; Pitsiladis, Yannis; Reisch, Lucia; Santaliestra-Pasías, Alba M; Maes, Lea; et al.
Abstract: Objective: The aim of the present study was to investigate if context-specific measures of parental-reported physical activity and sedentary behaviour are associated with objectively measured physical activity and sedentary time in children. Design: Cross-sectional study. Setting: Seven European countries taking part in the IDEFICS (Identification and Prevention of Dietary- and Lifestyle-induced Health Effects in Children and Infants) study. Subjects: Data were analysed from 2–9-year-old children ( n 5982) who provided both parental-reported and accelerometer-derived physical activity/sedentary behaviour measures. Parents reported their children's daily screen-time, weekly sports participation and daily outdoor playtime by means of the Outdoor Playtime Checklist (OPC) and Outdoor Playtime Recall Questions (OPRQ). Results: Sports participation, OPC- and OPRQ-derived outdoor play were positively associated with accelerometer-derived physical activity. Television viewing and computer use were positively associated with accelerometer-derived sedentary time. All parental-reported measures that were significantly associated with accelerometer outcomes explained only a minor part of the variance in accelerometer-derived physical activity or sedentary time. Conclusions: Parental-reported measures of physical activity and sedentary behaviour are not useful as a proxy for 2–9-year-old children's physical activity and sedentary time. Findings do not preclude the use of context-specific measures but imply that conclusions should be limited to the context-specific behaviours that are actually measured. Depending on the aim of the study, future research should carefully consider the choice of measurements, including the use of subjective or objective measures of the behaviour of interest or a combination of both.